Teaching Listening to Junior High School Students by Using Web Based Learning Resources (WBLR) - Sisri Ovalina; Aryuliva Adnan (Universitas Negeri Padang, 2018)
AbstractListening is a skill that has to be mastered by language students because it is the basis for communication. If the students do not understand what the interlocutors are saying, the communication will not happen even though they are good in speaking. However, when learning English, most students have difficulties in listening. Based on the previous research, it is because the teacher often skips to teach listening so the students are not used to listen, strategy used by the teacher is monotonous, and the speed of the speakers, and also the students are lack of vocabulary. To solve the problem, the writer wants to apply and explain a media called Web Based Learning Resources. Web Based Learning Resources is an interactive web-based tools that support learning by enhancing, amplifying, and guiding the cognitive processes of students. It requires students to do different exercises with authentic materials, and it will give feedback soon after the students finish the exercises. The finding shows WBLR can improve students learning skill since they are used to listen to the native speakers. Key words: Listening, Teaching Listening, Web Based Learning Resources